Leisure and Elite Formation Arenas of Encounter in Continental Europe, 1815-1914 - Kohlrausch, Martin 1973- (Elitenwandel in der Moderne / Elites and Modernity Ser., 2020)
The book series focus on the relevance and changing meaning of elites in late modern European history. The series addresses the persistence in power of the nobility and looks at the emergence of new elite formations in the context of the rise of mass media and social mobilization.